Medium chain fatty acid supplementation improves animal metabolic and immune status during the transition period: A study on dairy cattle - Wang, Zhonghan; Wang, Qianqian; Tang, Chuanlan; Yuan, Jing; Luo, Chenglong; Li, Dong; Xie, Tian; Sun, Xiaoge; Zhang, Yan; Yang, Zhantao; Guo, Cheng; Cao, Zhijun; et al. (Frontiers in Immunology, 2023)
The transition period is the stage of the high incidence of metabolic and infectious diseases in dairy cows. Improving transition dairy cows’ health is crucial for the industry. This study aimed to determine the effects of dietary supplementation medium-chain fatty acids (MCFAs) on immune function, metabolic status, performance of transition dairy cows. Twenty multiparous Holstein cows randomly assigned to two treatments at 35 d before calving. 1) CON (fed the basal 2) MCFA treatment (basal diet was supplemented at an additional 20 g MCFAs mixture every day) until 70 d after calving. The results showed that the serum amyloid A myeloperoxidase concentrations in the blood of cows in MCFA treatment significantly decreased during the early lactation (from 1 d to 28 d after calving) 0.03, 0.04, respectively) compared with the CON, while the tumor necrosis factor concentration was significantly decreased at 56 d after calving (P = 0.02). In addition, the concentration of insulin in the pre-calving (from 21 d before calving to calving) blood of cows in MCFA treatment was significantly decreased (P = 0.04), and concentration of triglyceride also showed a downward trend at 28 d after calving 0.07). Meanwhile, MCFAs supplementation significantly decreased the concentrations of lithocholic acid, hyodeoxycholic acid, and hyocholic acid in the blood at 1 d calving (P = 0.02, < 0.01, < 0.01, respectively), and the level of hyocholic acid taurocholic acid concentrations (P < 0.01, = 0.01, respectively) decreased dramatically at 14 d after calving. However, compared with the CON, the pre-calving dry matter intake and the early lactation milk yield in MCFA treatment were significantly decreased (P = 0.05, 0.02, respectively). In conclusion, MCFAs supplementation transition diet could improve the immune function and metabolic status of dairy cows, and the health of transition cows might be beneficial from the endocrine status.